Combined cord blood metabolomic and clinical signatures discriminate small for gestational age neonates in preeclampsia - Luhan Zhang; Weibo Huang; Shuyuan Xue; Xiaolan Chi; Gang Guo; Guifeng Ding (Frontiers in Endocrinology, 2026)
Background Preeclampsia (PE) subjects the fetus to a hostile intrauterine environment and elevates the risk of small for gestational age (SGA). The link between cord blood metabolic signs and PE exposure is still unclear. This connection may affect fetal growth. Methods We did untargeted metabolomics profiling of cord blood. This involved 37 pregnancies with preeclampsia (PE) and 48 control pregnancies. We used liquid chromatography-mass spectrometry for the analysis. Researchers examined metabolites that showed differential expression. They also analyzed pathway enrichment. We used Spearman’s correlation to assess associations between metabolites and clinical indicators, including birth weight. We created a discriminative model for SGA. It combines metabolic features and clinical variables. Results In the PE group, 205 metabolites changed significantly. Of these, 82 were upregulated and 123 were downregulated. Caffeine metabolism, lysine biosynthesis, and sulfur metabolism were the top three pathways affected. Among the dysregulated metabolites, 2-oxoadipic acid is important in lysine breakdown. It showed a strong negative link with birth weight ( r = -0.396, P < 0.001). Xanthine had positive links to gestational age at delivery ( r = 0.292, P = 0.007) and birth weight ( r = 0.219, P = 0.044). Lysine was positively correlated with maternal BMI at delivery ( r = 0.414, P < 0.001). Caffeine metabolites, like paraxanthine, theobromine, and theophylline, were enriched together. However, none showed a significant link to birth weight. The SGA discriminative model reached an AUC of 0.896 ( P < 0.01). Conclusions PE greatly changes the cord blood metabolome. This has a primary impact on caffeine, lysine, and sulfur metabolism. 2-Oxoadipic acid is linked to fetal growth restriction. Combining cord blood metabolic signatures with clinical data makes a strong model. These findings reveal metabolite-level disturbances that may help elucidate the metabolic basis of impaired fetal growth in preeclampsia.